Biogas to liquefied biomethane: Assessment of 3P's–Production, processing, and prospects. (March 2020) - Qyyum, Muhammad Abdul; Haider, Junaid; Qadeer, Kinza; Valentina, Valentina; Khan, Amin; Yasin, Muhammad; Aslam, Muhammad; De Guido, Giorgia; Pellegrini, Laura A.; Lee, Moonyong
Abstract: Sustainable scale-up of biomethane to overcome the dependency on fossil energy sources is still not matured, fundamentally owing to its production and availability at a lower pressure (i.e., atmospheric) compared with the conventional natural gas. This is a fundamental assessment that specifically aims to overview the biogas production, cleaning technologies, upgrading technologies, and possible biomethane liquefaction technologies. The digestion technologies for biogas production are analyzed in terms of their important operating and performance parameters corresponding to optimum digester operation. The cleaning and upgrading technologies are assessed corresponding to their competitive factors, merits, and associated challenges. Cryogenic separation relies on different technologies that are based on different mechanisms (anti-sublimation, distillation, etc.). These technologies have been recently studied for CO2 removal from high CO2 -content natural gas, showing promising results for application to biogas upgrading, in particular if the final goal is liquefaction. Since liquefaction itself is an energy- and cost-intensive process, cryogenic separation is synergistic in obtaining upgraded and liquefied biomethane in a single process unit, instead of integrating liquefaction with other upgrading technologies. Among all available liquefaction technologies, the nitrogen expander-based liquefaction processes are most promising candidates to produce liquified biomethane (LBM), mainly due to small investment costs, simple operation, and compact design. This study suggests that there is a need to design energy-efficient small-scale biomethane liquefaction processes following biogas upgrading. Thus, incorporating biogas in the energy mix would result in economic, environmental, and climate benefits, globally. Graphical abstract: Image 1 Highlights: An assessment of liquefied biomethane supply chain is presented. Biogas digestion systems along with their performance parameters are analyzed. A comparative features of typical approaches to upgrade biogas to biomethane. Liquefaction is suggested for the feasible and economic transportation of biomethane. Challenges and future research directions of biogas industry are identified.